Diagnostic utilities of tracheal ultrasound and USB-endoscope for the confirmation of endotracheal tube placement: A cadaver study - DENİZBAŞI ALTINOK, ARZU; SANRI, ERKMAN; AKOĞLU, HALDUN; KARACABEY, SİNAN; ŞEHİRLİ, ÜMİT SÜLEYMAN; VERİMLİ, URAL (W B SAUNDERS CO-ELSEVIER INC, 2018)
Objectives: Confirmation of the endotracheal tube placement (CoETP) has the utmost importance in the management of an airway. Visualization of tracheal rings or carina with a fiber-optical bronchoscope (FOB) has considered to be a reliable method for the CoETP. However, FOB is expensive, time-consuming, and not always practical. Inexpensive endoscopic USB-cameras were shown to aid intubation successfully and reliably. On the other hand, there have been no studies investigating their use for the CoETP. Tracheal ultrasonography (TUS) is also a new, inexpensive and widely available alternative. A cadaver study has planned to evaluate the diagnostic utility of TUS and a USB-camera. Methods: This study was conducted in the Anatomy Lab of a University on a fresh frozen female cadaver. Three senior Emergency Physicians have intubated the cadaver, and performed TUS or USB-endoscopy. We have prepared a randomized intubation list (n = 96) in three blocks (3 times 32) as to include equal number of esophageal and tracheal intubations (48 for each). Each EP is performed all three interventions (intubation, TUS and USB-endoscopy) in consecutive blocks of 32 intubations, in turn. The position of the tube has been verified from a 2 cm wide ostium on the proximal trachea. Results: In this study, all intubations (n = 96, 100%) were correctly identified as tracheal or esophageal with both TUS and USB-camera. Both the sensitivity and specificity of TUS and USB-endoscopy for the CoETP were 100.0%. Conclusion: The perfect accuracy of TUS and USB-endoscopy, have placed those techniques in a unique position as an alternative in resource-poor situations. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Endotracheal intubation; Cadaver; Tracheal ultrasonography; Fiberoptic bronchoscopy; Borescope; USA-endoscopy; EMERGENCY-DEPARTMENT; INTUBATION; POSITION; ULTRASONOGRAPHY; VERIFICATION; METAANALYSIS